2015
DOI: 10.3923/tasr.2015.207.215
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Gender and Age and Flat Foot in Obese Children

Abstract: The purpose of this study was to detect the correlation between age and gender with flat foot deformity in obese children. One hundred fifty children ranged in age from 8-14 years participated in this study. They were selected according to body mass index to be obese children, then they were divided according to gender into two groups, group I and group II (75 boys and 75 girls), then each group divided according to age into equal three sub groups (from 8-10 years, from 10-12 years and from 12-14 years) each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
5
11
3
2
Order By: Relevance
“…The current study shows that the prevalence percentage of flat foot among the total population is 61.76%, two times greater than healthy foot [14][15][16][17]. Flat feet were high in males than females, the prevalence of flat feet was 50.98% in males and 10.78% in females.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The current study shows that the prevalence percentage of flat foot among the total population is 61.76%, two times greater than healthy foot [14][15][16][17]. Flat feet were high in males than females, the prevalence of flat feet was 50.98% in males and 10.78% in females.…”
Section: Discussionmentioning
confidence: 77%
“…This scanner can tackle shortage of wet foot test which is not accurate because of the difficulty of knowing that the subjects are standing in upright position when printing their foot at a piece of paper [22]. But the method for classifying foot types by Cavanagh's arch index is rather difficult compared to the Staheli's arch index [7] [15]. From the result of this study which showed that significant correlation between AI and RFA, classifying foot types can be done simpler only by measuring LFA using flatbed document scanner and ULFA using 3D scanner compared to the Cavanagh's arch index.…”
Section: Discussionmentioning
confidence: 99%
“…In most researches, boys were claimed to have a higher prevalence of flatfoot than girls. Hazzaa et al 15 reported that the proportion of flatfoot in male was 52% and female was 49%.…”
Section: Discussionmentioning
confidence: 99%
“…6 , el 19,1 % de Jerosch y cols. 4 La desigual aceptación de la revisión en consulta entre las niñas (69,23 %) y los niños (35,51 %) condicionó el resultado de 11/4 niñas/niños seleccionados, contradiciendo la mayor prevalencia del pie plano flexible en niños reportado por numerosas investigaciones 2,7,27,28 , que algunos autores las relacionan a factores como edad temprana, sobrepeso, laxitud articular o sedentarismo 2,7,27,28,29 . La no existencia de diferencias significativas en la edad, peso, altura, PRCA, IMC, IPP-6, asociadas al sexo, podría interpretarse como una adecuada homogeneidad de la muestra.…”
Section: Discussionunclassified